2019
DOI: 10.1093/jxb/erz185
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide accelerates germination via the regulation of respiration in chickpea

Abstract: Seed germination is crucial for the plant life cycle. We investigated the role of nitric oxide (NO) in two chickpea varieties that differ in germination capacity: Kabuli, which has a low rate of germination and germinates slowly, and Desi, which shows improved germination properties. Desi produced more NO than Kabuli and had lower respiratory rates. As a result of the high respiration rates, Kabuli had higher levels of reactive oxygen species (ROS). Treatment with the NO donor S-nitroso-N-acetyl-D,L-penicillam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 61 publications
3
31
0
Order By: Relevance
“…It is undeniable that seed germination requires abundant energy and carbon skeletons [8,23,43]. Seeds store oil in the form of TAG in oleosomes to meet the energy demand of heterotrophic-to-autotrophic conversion during seed germination and seedling formation [44,45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is undeniable that seed germination requires abundant energy and carbon skeletons [8,23,43]. Seeds store oil in the form of TAG in oleosomes to meet the energy demand of heterotrophic-to-autotrophic conversion during seed germination and seedling formation [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Extensive studies have suggested that normal utilization of seed storage reserves and efficient energy supply are necessary for successful germination [22,23]. Carrot seeds are dicotyledonous and have an endosperm with high oil content (mainly in the form of triacylglycerol) [24], which is used as an energy source for germination [25].…”
Section: Introductionmentioning
confidence: 99%
“…For example, increased leaf area of the hybrid plant Arabidopsis resulted in increased biomass (Fujimoto et al, 2012). Improved germination was observed in the hybrid plant of chickpea because of its reduced ROS level (Pandey et al, 2019). In addition, hybrids showed obvious heterosis for photosynthesis under salt stress (Xu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, breeding new hybrid crops is one of the most effective strategies to promote salinity tolerance of B. napus plants. A recent report showed the important role of NO in hybrid chickpea during the germination period without environmental stress (Pandey et al, 2019). The aims of this study were to cultivate new varieties with better salinity tolerance in the near future, and most importantly, explain the molecular mechanism in heterosis of salinity tolerance: the involvement of NO signaling.…”
Section: Introductionmentioning
confidence: 96%
“…For example, the aspartic acid family of amino acids contributes to the onset of autotrophic growth-associated processes during germination [13]. An exogenous nitric oxide donor (S-nitroso-N-acetyl-d,l-penicillamine) can enhance the germination of Kabuli chickpea seeds, which coincides with an increase in amino acid levels [57]. Exogenous H 2 O 2 also promotes the germination of eggplant seeds, accompanied by enhanced amino acid biosynthesis and protein expression [58].…”
Section: Discussionmentioning
confidence: 99%